Impact of Family Physicians' Practices upon the Quality of Family Medicine Health Care Services at Model Primary Health Care Centers in Baghdad City - Khalifa, hakam; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To evaluate the family physicians' practices and to measure its impact upon the quality of familymedicine health care in Baghdad City model primary health care centers.Methodology: A descriptive study, using the evaluation approach, has evaluated the impact of family physicians'practices upon quality of healthcare in Baghdad's Model Primary Health Care Centers of Family Medicine. It iscarried out during 15th of May – 20th of August 2017. The study is conducted at five model primary health carecenters of family medicine from two districts; AL-Rusafa and AL-Kurkh. Sample size is calculated to be (76)family physicians. Convenient sample of (124) patients who are attending these primary health care centers to seekfamily health care services. Adopted structured self-administered questionnaire is used to collect data from theFamily physicians. The list of dual-forced items obtained through the Delphi process, which include "Do" or "Don'tdo". Inpatient care is clarified with (25) statements, urgent care and minor procedures tested in (27) statements andambulatory care includes (16) statements. The quality of health care questionnaire is developed for the purpose ofthe study. The overall number of items included in the questionnaire is (18) items. Internal consistency "split-half"reliability is obtained through computation of Cronbach's alpha correlation coefficient. Content validity of thequestionnaire is determined through panel of (10) experts. Data are collected through the utilization of thequestionnaire and the interview technique as means of data collection. Data of both stages is entered to computerusing Statistical Package of Social Science, Version (23.00) for windows(10) (SPSS-23) and are handled usingdescriptive statistical data analysis approach (frequencies, percentages, mean of scores, total scores and Cronbach'salpha correlation coefficient) and inferential statistical data analysis approach (simple linear regression).Results: The study reveals that the majority of the family physicians has performance experienced inadequate offamily health care practices. The quality of family medicine health care services in Baghdad's primary health carecenters of the patients' perspectives is poor (82.30%).The impact of family physicians' practices upon the quality offamily medicine health care services in Baghdad City model primary health care centers presents that familyphysicians' practices have not made noteworthy change on the quality of family medicine health care services.Recommendations: Family physicians can follow the family medicine practices' standards to provide quality offamily medicine health care services. The Ministry of Health Department of Primary Health Care can periodicallymonitor the implementation of family physicians' practices standards for the benefit of better quality of familymedicine health care services. The family medicine quality of health care services can be valued on a regular basefor the benefits of the patients who are attending the primary health care centers to seek such care